2010
DOI: 10.3127/ajis.v16i2.592
|View full text |Cite
|
Sign up to set email alerts
|

The greening of organisational IT: what makes a difference?

Abstract: The trend towards green information technology (IT) over the last few years is a result of an acknowledgement of both the environmental impact of IT and the role IT plays as a potential source of solutions to environmental concerns. As organisations are under increasing pressures to act sustainably, environmental considerations are taking greater importance for organisations and the organisations" information systems (IS) and IT. This paper introduces a model proposing competitive pressures, legitimation press… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(40 citation statements)
references
References 26 publications
0
40
0
Order By: Relevance
“…To date, apart from Brown et al (2005), Chen et al (2008), Maruster et al (2008), Huang (2009), Ghose et al (2009), Kuo and Dick (2009) and Molla et al (2009) there have been few studies on Green IT reported in top tier Information Systems journals. This is probably a reflection on the time lag inherent in the academic publication cycle.…”
Section: Academic Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…To date, apart from Brown et al (2005), Chen et al (2008), Maruster et al (2008), Huang (2009), Ghose et al (2009), Kuo and Dick (2009) and Molla et al (2009) there have been few studies on Green IT reported in top tier Information Systems journals. This is probably a reflection on the time lag inherent in the academic publication cycle.…”
Section: Academic Researchmentioning
confidence: 99%
“…Applying institutional theory, Butler and Daly (2009) developed a series of theoretical propositions and argue that regardless of whether it is an interest in Green IT or in cost reduction, the concerns of business and IT managers are modulated by regulative, normative, and cultural-cognitive influences in the institutional environment. In a similar vein, a theoretical model was developed and tested by Kuo and Dick (2009) who found that initiatives are more likely to be motivated from a sense of social responsibility from empowered employees rather than as a response to external legitimation pressures or pursuit of competitive advantage.…”
Section: Academic Researchmentioning
confidence: 99%
“…Staff willingness to play an active role in developing sustainable ICT capability Kuo and Dick (2009) suggest that sustainable ICT efforts are motivated by employees' sense of social responsibility within adaptable organizations rather than by issues of economics and technologies. Staff willingness to participate and play an active role in sustainable ICT initiatives determines the successful development of sustainable ICT capability.…”
Section: Figure 6: Staff Perception Of the Importance Of Sustainabilimentioning
confidence: 99%
“…Rather than using the entire, huge amount data, it is more effective to conduct analysis by selecting data that conform to the purpose of the study, and IT is essential in dealing with environmental data that are increasing in such a way [33]. In addition, effective analysis of natural/environmental Big Data related to sea level rise, coastal erosion, floods, etc., is also very useful in disaster prevention [2,34,35]. Not only is IT effectively used in the analysis of such environmental data, but it is also closely associated with Geographic Information Systems, which are used for the comprehensive analysis of each region's land use, geological constraints, generation quantities, access roads, existing electrical grids, etc., which are used for selecting the optimum location of renewable energy generation facilities [36].…”
Section: Classification Of Big Data For the Effective Utilization Of mentioning
confidence: 99%
“…Green IT is a compound word from green, meaning eco-friendly, and information technology (IT). At first, the meaning of green IT was recognized as eco-friendly improvement to the issues of IT itself, such as the energy efficiency of data centers or resolving environmental issues through waste recycling of IT equipment [1][2][3][4][5]. This is called "Green for IT" or "Green IT 1.0".…”
Section: Introductionmentioning
confidence: 99%